An Extension of the Second Welfare Theorem to Economies with Nonconvexities and Public Goods - Khan, M. Ali; Vohra, Rajiv (Quarterly Journal of Economics, 1987)
In this paper we report a generalization of the results of Foley and Guesnerie on the second welfare theorem to economies with arbitrary nonconvex production sets. The nature of marginal cost prices in such economies is clarified through the use of the Clarke tangent cones.